Proposing a method to design secure digital signature scheme on the ring structure Zn - Truong, Nguyen Dao; Tuan, Le Van (Journal of Science and Technology on Information security, 2022)
Abstract— In this paper, we propose a method to design signature scheme on ring structure with residual classes modulo composite. At the same time, we develop several new digital signature schemes that are more secure, with faster signature generation than ElGamal digital signature scheme and its variants. Furthermore, our proposed signature scheme has overcome some weaknesses of some published signature scheme of the same type, which are built on ring structure.